Pengaruh Inovasi Produk Dan Harga Terhadap Keputusan Pembelian Femishion.id di Industri Kemeja Wanita Online - Anastasia Irawati; Muhammad Syihabuddin (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aims to analyze the influence of product innovation and price on consumer purchasing decisions at Femishion.id, an online fashion business specializing in women’s shirts marketed through e-commerce platforms such as Shopee, TikTok, and Instagram. The primary issue addressed in this research is the decline in active consumers and the increasing competition within the online fashion industry, which requires companies to enhance product innovation and adopt competitive pricing strategies. A quantitative research method was employed by distributing questionnaires to 69 respondents who had previously purchased products from Femishion.id. The research instruments were tested using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis to determine both partial and simultaneous effects of the variables. The results indicate that product innovation and price have a positive and significant effect on consumer purchasing decisions, both partially and simultaneously. Price emerges as the most dominant factor influencing consumer behavior. Overall, 71.7% of the variance in purchasing decisions is explained by the two variables. These findings highlight that the combination of trend-aligned product innovation and competitive pricing is crucial in shaping purchasing decisions within the online women’s fashion industry. In conclusion, Femishion.id needs to prioritize updating product designs and maintaining price strategies that align with consumer purchasing power to sustain its competitive advantage.